Isolation of Poly-β-hydroxybutyrate (PHB) Producing Bacteria from Sago Dregs and Sugarcane Solid Waste - Syalsa Aulia Putri; Muhammad Fiqriansyah Wahab; Arsad Bahri (Universitas Negeri Makassar, 2021)
Soil is the habitat of thousands of microscopic organisms, especially bacteria. Soil containing sago waste is rich in carbon sources and potentially as a raw material for the manufacture of Poly-β-hydroxybutyrate (PHB). Biodegradable plastic is one of the eco-friendly plastic materials, this type of plastic is made with Poly-β-hydroxybutyrate (PHB) as the raw material. Sago waste is usually not utilized to the maximum. The purpose of this study was to obtain isolates of poly-β-hydroxybutyrate (PHB) producing bacteria from sago pulp waste without the addition of bacterial agents from the outside environment. This research was conducted in the Laboratory of Microbiology FMIPA UNM. Soil samples with sago dregs were obtained from a sago processing plant in Takalar, South Sulawesi. Bacteria are isolated by dilution serialized three times then grown on medium Nutrient Agar and purified on medium Strach Agar then fermented with Ramsay medium. The results showed the presence of biodegradable plastic formed in the breeding medium.